2022
DOI: 10.3390/ijms23137235
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of AlphaFold2 to Predict MFS Protein Conformations after Selective Mutation

Abstract: The major facilitator superfamily (MFS) is the largest secondary transporter family and is responsible for transporting a broad range of substrates across the biomembrane. These proteins are involved in a series of conformational changes during substrate transport. To decipher the transport mechanism, it is necessary to obtain structures of these different conformations. At present, great progress has been made in predicting protein structure based on coevolutionary information. In this study, AlphaFold2 was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Although previous studies suggested that AF2 is unable to predict point mutations that cause misfolding or destabilization of the native structure, , the situation is different for the protein conformational change because AF2 can learn alternative conformations of homologous proteins in PDB. A previous study also showed a possibility that two or more mutations allow AF2 to explore an alternative conformation of transporter proteins . In combination with the accelerated MD simulation, we here clarified that even a single mutation in AF2 can shift the predicted conformation.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Although previous studies suggested that AF2 is unable to predict point mutations that cause misfolding or destabilization of the native structure, , the situation is different for the protein conformational change because AF2 can learn alternative conformations of homologous proteins in PDB. A previous study also showed a possibility that two or more mutations allow AF2 to explore an alternative conformation of transporter proteins . In combination with the accelerated MD simulation, we here clarified that even a single mutation in AF2 can shift the predicted conformation.…”
supporting
confidence: 70%
“…A previous study also showed a possibility that two or more mutations allow AF2 to explore an alternative conformation of transporter proteins. 42 In combination with the accelerated MD simulation, we here clarified that even a single mutation in AF2 can shift the predicted conformation. Furthermore, we showed that AF2 prediction is affected by the input MSA, and residuewise coevolution score derived from the MSA can pin down the state-shifting mutations.…”
mentioning
confidence: 66%
“…Mining sites of interaction/flexibility ( Zhang et al, 2020 ) that can be mutated to produce, or induce AF2 modeling of, alternate conformers ( Bozzi et al, 2016a ; Bozzi et al, 2016b ; Del Alamo et al, 2022 ; Stein and Mchaourab, 2022 ; Xiao et al, 2022 ) should be useful to represent the spectrum of conformational diversity in the Slc11 family, and comparative analyses across phylogroups will aid probing the dynamics of Slc11 carrier cycle and its plasticity throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also showed a possibility that two or more mutations allow AF2 to explore an alternative conformation of transporter proteins. 38 In combination with the accelerated MD simulation, we here clarified that even a single mutation can shift AF2-predicted conformation. Furthermore, we showed that AF2 prediction is affected by the input MSA, and residue-wise coevolution score derived from the MSA can pin down the state- shifting mutations.…”
Section: Main Textmentioning
confidence: 67%